Художник – час – мистецький образ (живописний ансамбль золочівської церкви св.Миколая) - Грималюк, Р. (Інститут народознавства НАН України, 2007)
Modest Sosenko, author of monumental paintings, had been thoughtful gifted artist, connoisseur in aesthetics of church murals applicable at contemporary temples and bright representative of creators’ pleiad that in early XX c. made firm steps toward propagation of present — day Ukrainian aestheticism. To Sosenko’s brush belong paintings in 11 churches of the Western Ukraine. His keen interest in traditional folk ornaments, particularly Hutsul (embroided, woven and carved) and Poltavan (stitched) ones had become quite powerful source of inspiration for works in St. Nicholas Church at Zolochiv.